Stress and Traditional Support: The Role of Orphans’ and Vulnerable Children’s Primary Caregivers in Rural Ethiopia - Aweke Tadesse; Kenan Li; Jesse Helton (Children)
Background/Objectives: Orphans’ and Vulnerable Children’s (OVC) primary caregivers (PCGs) in Ethiopia live with multiple social and emotional problems stemming from extreme poverty, war, environmental disasters, and the HIV pandemic. Family and community supports are strained, leaving OVC’s PCGs dependent on inconsistent humanitarian aid. This aid is typically focused on OVCs and does not address PCG well-being. This study aimed to assess PCG well-being and explore their perceived stress and the traditional family and community coping mechanisms. Method: Participants from the Oromia region of Ethiopia were recruited, and a mixed-methods design was employed. Six cases were included using a criterion sampling technique. An explanatory data analysis technique was used, and data were triangulated from interviews, focus group discussions, archival information, and surveys. A 36-item Well-being Measuring Tool (WMT) Likert scale was employed to measure well-being domains. Result: The results indicated that none of the PCGs reported the desirable and average summative well-being domain mean scores [25 and 23]. Among the ten well-being domains, only “spirituality” and “community cohesion” were above the average score [2.3]. The “economy” domain had the lowest score, indicating a critical deficiency [1.3]. A lack of community support could exasperate perceived stress, and well-being deficiencies were linked. Conclusions: Lack of family and community support could exacerbate feeling overlooked, unwelcome, and lonely. A policy that promotes a supportive community environment and safeguards the most vulnerable OVCs and their PCGs should be in place. This study recommends further rigorous research examining the well-being determinants of OVCs’ PCGs in Ethiopia and the role of traditional support systems in rural settings.